Urinary Fatty Acid Binding Protein 3 Has Prognostic Value in Peripheral Artery Disease - Li, Ben; Zamzam, Abdelrahman; Syed, Muzammil H.; Jahanpour, Niousha; Jain, Shubha; Abdin, Rawand; Qadura, Mohammad (Frontiers in Cardiovascular Medicine, 2022)
Background: Despite its significant association with limb loss and death, peripheral artery disease (PAD) remains underdiagnosed and undertreated. The current accepted gold-standard for PAD screening, the ankle brachial index (ABI), is limited by operator dependence, erroneous interpretation, and unreliability in patients with diabetes. Fatty acid binding protein 3 (FABP3) is an intracellular protein that becomes released into circulation and excreted into urine following skeletal muscle injury. We examined the prognostic ability of urinary FABP3 (uFABP3) in predicting adverse peripheral artery disease (PAD)-related events. Methods: In this prospective case-control study, urine samples were collected from patients with PAD (n=142) and without PAD (n=72). The cohort was followed for 2 years. uFABP3 was normalized to urinary creatinine (uCr) (uFABP3/uCr). The primary outcome was major adverse limb event (MALE; composite of vascular intervention [open or endovascular] or major limb amputation). The secondary outcome was worsening PAD status (drop in ABI≥0.15). Cox regression analyses with multivariable adjustment for baseline demographic and clinical variables were performed to assess the prognostic value of uFABP3/uCr with regards to predicting MALE and worsening PAD status. Results: Patients with PAD had significantly higher median [IQR] uFABP3/uCr levels (3.46 [2.45–6.90] vs. 2.61 [1.98–4.62], p=0.001). MALE and worsening PAD status were observed in 21 (10%) and 28 (14%) patients, respectively. uFABP3/uCr predicted MALE and worsening PAD status with adjusted hazard ratios (HR) of 1.28 (1.16–1.41, p=0.001) and 1.16 (1.02–1.27, p = 0.021), respectively. Patients with high uFABP3/uCr had a lower 2-year freedom from MALE (86% vs. 96%, p=0.047) and worsening PAD status (78% vs. 99%, p=0.001). There was good discriminatory ability for uFABP3/uCr in predicting the primary outcome of MALE, with an area under the receiver operating characteristics curve (AUROC) of 0.78. Conclusions: Measuring uFABP3/uCr levels in patients with PAD can help identify those at high risk of adverse PAD-related events. This study highlights the prognostic value of uFABP3 in risk-stratifying individuals for further diagnostic vascular evaluation or aggressive medical management.